Electrochemical oxidation of the poultry manure anaerobic digested effluents for enhancing pollutants removal by Chlorella vulgaris - Wang, Mengzi (Environmental technology, 2016)
The mechanisms and pseudo-kinetics of the electrochemical oxidation for wastewater treatment and the synergistic effect of combining algal biological treatment were investigated. NaCl, Na2SO4 and HCl were applied to compare the effect of electrolyte species on nutrients removal. NaCl was proved to be more efficient in removing ammonia ([Formula: see text]), total phosphorus (TP), total organic carbon (TOC) and inorganic carbon (IC). [Formula: see text] oxidation by using Ti/Pt-IrO2 electrodes was modelled, which indicates that the [Formula: see text] removal followed the zero-order kinetic with sufficient Cl(-) and the first-order kinetic with insufficient Cl(-), respectively. The feasibility of combining electrochemical oxidation with microalgae cultivation for wastewater treatment was also determined. A 2 h electrochemical pretreatment reduced 57% [Formula: see text], 76% TP, 72% TOC and 77% IC from the digested effluent, which is applied as feedstock for algae cultivation, and resulted in increasing both the biomass production and pollutants removal efficiencies of the algal biological process